2017
DOI: 10.2141/jpsa.0160088
|View full text |Cite
|
Sign up to set email alerts
|

Egg Envelope Glycoproteins ZP1 and ZP3 Mediate Sperm-Egg Interaction in the Japanese Quail

Abstract: Fertilization is indispensable for zygotic formation leading to the birth of animals and the species-specific spermegg binding thought to be the initial step in this important process. In birds, the oocyte, which encounters the spermatozoa at the time of fertilization, is enclosed in a perivitelline membrane (pvm) constructed of several zona pellucida glycoproteins (ZP proteins: ZP1, ZP2, ZP3, ZP4 and ZPD). The aim of this study was to determine the ZP protein in the pvm responsible for sperm-pvm binding in Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Additional research will be necessary to determine whether ZPB2 acts as a sole sperm receptor or if it works in concert with other ZP proteins such as ZPA, ZPB1, ZPC or ZPD to form the requisite sperm receptor complex. Although ZPB1, ZPC and ZPD have been reported to bind sperm in one or more avian species [16,27,28], none of these ZP proteins have a greater expression in the GD region relative to the NGD region. Only ZPB2 in the current study, and ZPA, as previously reported [25], are associated with higher expression in the GD region.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additional research will be necessary to determine whether ZPB2 acts as a sole sperm receptor or if it works in concert with other ZP proteins such as ZPA, ZPB1, ZPC or ZPD to form the requisite sperm receptor complex. Although ZPB1, ZPC and ZPD have been reported to bind sperm in one or more avian species [16,27,28], none of these ZP proteins have a greater expression in the GD region relative to the NGD region. Only ZPB2 in the current study, and ZPA, as previously reported [25], are associated with higher expression in the GD region.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, the expression of ZPB2 mRNA is greater in immature white follicles, and the expression of ZPB2 mRNA was reported to be significantly greater in the GD granulosa cells when compared with the NGD granulosa cells in F 1 and F 2 follicles in turkey hens [19], suggesting that it may also be a factor in the preferential binding of sperm to this region of the IPVL. Additional research suggests that avian ZPB1 and ZPC may be involved in sperm binding to the IPVL or the initiation of the acrosome reaction [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Sperm-egg binding is an initial step toward subsequent events such as AR, penetration into the egg extracellular envelope, and fusion with the egg plasma membrane. It is a shared feature between mammals and birds that ZP and IPVL components contain the receptor for respective sperm (Bleil and Wassarman, 1980;Han, et al, 2010;Ichikawa, et al, 2017). Sperm surfaces possess numerous molecules with a high binding affinity to ZP in mammals.…”
Section: Membrane Regulation Of Sperm-egg Binding and Acrosome Reactionmentioning
confidence: 99%
“…Tanaka et al (1994) produced viable chicks by implanting ova 2 that were inseminated in vitro into the oviducts of recipient hens. We previously demonstrated the binding and penetration of multiple sperm into an isolated perivitelline membrane (pvm), the extracellular coat surrounding the egg, in Japanese quail (Sasanami et al, 2012;Ichikawa et al, 2017). We also successfully produced quail chicks using ICSI and subsequent ex ovo culture without implantation into the oviduct (Mizushima et al, 2014).…”
Section: Introductionmentioning
confidence: 99%